PENGGUNAAN MEDIA FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF PADA KELAS 1 SEKOLAH DASAR - Meliani, - (2022)
Recognizing letters is the ability of students to recognize the characteristics of the alphabet that symbolizes the pronunciation of a language that recites the letters repeatedly. This research was motivated by the initial ability test which stated that the ability to recognize letters was still low. This is due to the lack of use of methods and media. To deal with these problems, researchers applied flashcard media to help students remember letters and read simple vocabulary. The purpose of this study is to describe the use of flashcard media in early reading learning and to determine the level of ability to recognize letters in grade 1 using flashcard media. This research was conducted to overcome the problem of students' difficulty recognizing letters. This research method is a mixed method with a triangulation research design. Data collection techniques are tests, observations, interviews, field notes and documentation. The results of the pretest and posttest data were normally distributed and the average difference was 0.000. So the p-value (2-tailed) = 0.000 and the result is less than the significance level of (0.05). It states that H_1 is accepted. So there is a difference between the pretest and posttest data. The increase in the average n-gain index from the pretest and posttest, which is 0.73 is classified as high category. It can be concluded, there is an increase from the pretest data to the posttest using flashcard media. Keywords: recognize letters, early reading, flashcard media